2019
DOI: 10.1002/hyp.13370
|View full text |Cite
|
Sign up to set email alerts
|

Improving the SWAT forest module for enhancing water resource projections: A case study in the St. Croix River basin

Abstract: Insufficiently calibrated forest parameters of the Soil & Water Assessment Tool (SWAT) may introduce uncertainties to water resource projections in forested watersheds. In this study, we improved SWAT forest parameterization and phosphorus cycling representations to better simulate forest ecosystems in the St. Croix River basin, and we further examined how those improvements affected model projections of streamflow, sediment, and nitrogen export under future climate conditions. Simulations with improved forest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 62 publications
(104 reference statements)
0
5
0
Order By: Relevance
“…The soil and water assessment tool (SWAT) ecohydrological models have a strong physical mechanism, which simulating and analyzing the temporal and spatial changes of hydrological processes such as interception, evapotranspiration, infiltration, surface runoff and groundwater runoff from the time scale of a year, month and day [33][34][35]. Moreover, the SWAT can reflect the spatiotemporal variability of climate factors and the underlying surface and has been widely applied in the research of forest hydrology [36,37]. Therefore, the combination of the SWAT model and water balance method can quantitatively analyze the multitime scale characteristics of forest water conservation [38].…”
Section: Introductionmentioning
confidence: 99%
“…The soil and water assessment tool (SWAT) ecohydrological models have a strong physical mechanism, which simulating and analyzing the temporal and spatial changes of hydrological processes such as interception, evapotranspiration, infiltration, surface runoff and groundwater runoff from the time scale of a year, month and day [33][34][35]. Moreover, the SWAT can reflect the spatiotemporal variability of climate factors and the underlying surface and has been widely applied in the research of forest hydrology [36,37]. Therefore, the combination of the SWAT model and water balance method can quantitatively analyze the multitime scale characteristics of forest water conservation [38].…”
Section: Introductionmentioning
confidence: 99%
“…The results focus on three key water balance terms: ET, water yield, and amount of water in the soil profile. We used CO 2 concentrations of 330 ppm for the base period (Jha et al 2006;Wu et al 2012), 490 (RCP4.5) and 575 ppm (RCP8.5) for the mid-century period, and 522 (RCP4.5) and 838 ppm (RCP8.5) for the end-century period (Yang et al 2018). The base conditions (base period), mid-century and end-century are defined as the 1961-2000, 2046-2065, and 2081-2099 time periods, respectively.…”
Section: Downscaled Future Climate Datamentioning
confidence: 99%
“…The average atmospheric CO 2 concentrations were obtained from the literature. We used CO 2 concentrations of 330 ppm for the base period (Jha et al 2006;Wu et al 2012), 490 (RCP4.5) and 575 ppm (RCP8.5) for the mid-century period, and 522 (RCP4.5) and 838 ppm (RCP8.5) for the end-century period (Yang et al 2018). Unavailable weather data for historical simulations and future projections such as humidity, solar radiation, and wind speed were generated by the SWAT weather generator file (Arnold et al 2012).…”
Section: Journal Of the American Water Resources Associationmentioning
confidence: 99%
“…Evaluations for all times forecasted that the maximum and the minimum temperatures will rise to 6.6 and 2.99 • C in Representative Concentration Pathway (RCP) scenarios and rainfall in all periods raised by 40.32% and +40%, respectively. Young et al 23 studied the development of forest modeling by the SWAT model to increase the accuracy of water resource prediction in the St.…”
Section: Introductionmentioning
confidence: 99%
“…Young et al 23 studied the development of forest modeling by the SWAT model to increase the accuracy of water resource prediction in the St. Croix River Watershed and concluded that SWAT forest ecosystem characterization in water prediction, sedimentation, and nutrient delivery from the river improved the results.…”
Section: Introductionmentioning
confidence: 99%